AB1183 Myofascial involvement an unusual manifestation suggestive of systemic autoinflammatory diseases (AID): The description of three pediatric patients. (23rd January 2014) - Ughi, N.; Romano, M.; Donati, C.; Del Giudice, E.; Gattinara, M.; Pontikaki, I.; Meroni, P.L.; Gerloni, V.
Abstract : Background: AIDs are a group of heterogeneous disorders characterized by recurrent fever and systemic inflammation (aseptic and non-autoimmune). Myalgia is a common manifestation, frequently associated with erythematous macular rash Objectives: To describe the clinical, magnetic resonance imaging (MRI) and pathologic findings of myofascial involvement in AIDs Methods: In 3 children with AIDs and unusual disabling myalgias, muscle involvement was investigated by biopsy and MRI Results: All pts were Caucasian, two boys (4 and 5 year old, Case 1 and 2 respectively) and one girl (10 year old, Case 3), and presented with rash on limbs and eyelids, spiking fever, fatigue, and disabling myalgias, seldom blunt arthritis. Moreover, Case 2 developed annular eruptions on limbs and a maculopapular rash on palms and soles, while Case 3 had urticaria-like manifestations and arthritic episodes confirmed by ultrasounds (joint effusions and synovitis) with no erosions on X-Rays. Lab tests showed anaemia, thrombocytosis, high ESR and CRP, and extremely raised ferritin (10400-30140 ng/mL). Immunologic tests were negative. A diagnosis of AID was suspected. In relation to the unusual myalgias, muscular involvement was investigated: very high aldolase levels were detected (42.8-53.6 U/L, normal <7.6) with normal CPK. Then, MRI of the thighs in 2 pts (Case 2 and 3) displayed edema of subcutis and fascia and in Case 3 likely epimysial edema, too. Thereafter, all 3 thigh muscle biopsies showed aspecific inflammatory findings without direct myocytic involvement (Case 1 monocytic fasciitis, Case 2 perimyocitic inflammatory infiltrate, Case 3 perivascular lymphocytes and interstitial edema of skin and fascia). In Case 2 AID was confirmed by genetic analysis (mutations in exones 2, 3, 4 and 6 of TNFRSF1A and exone 3 of NLRP3 genes suggestive of TNF receptor-associated periodic syndrome [TRAPS]), while there were no specific findings in Case 1, the analysis is ongoing in Case 3. All 3 pts were treated with pulse i.v. methylprednisolone and oral steroids with clinical and inflammatory indexes amelioration. Anti-IL1 Anakinra was introduced in Case 1 and 2 with steroid sparing and obtaining complete resolution of myalgias and control of fever and rash. Lab tests improved as well. In Case 3 Cyclosporine A was started with no efficacy. Therefore, Anakinra was added showing partial response, but stopped because of reaction on injection site. Then, antiTNF Etanercept was used with no response, so all therapies were substituted for oral steroids with improvement of symptoms and Lab tests. A trial with anti-IL1 Canakinumab is on evaluation Conclusions: Myalgias and severe disabling muscle pain, associated with a sharp increase in muscle-specific enzyme aldolase, seem highly suggestive of AID and may result from myofascial involvement rather than myositis. At our knowledge, similar feature are described in only few adult pts [1] and no pediatric cases of documented myofascial involvement are described so far References: KM Hull, et al, Arthritis Rheum. 2002;46(8):2189-94. Disclosure of Interest: None Declared